2021
DOI: 10.1111/sltb.12784
|View full text |Cite
|
Sign up to set email alerts
|

Experiential avoidance in non‐suicidal self‐injury and suicide experiences: A systematic review and meta‐analysis

Abstract: Introduction:This systematic review and meta-analysis aimed to (i) examine the associations between experiential avoidance (EA), non-suicidal self-injury (NSSI), and suicide experiences, and (ii) identify sample-and methodological-related variables affecting the strength of these associations. Method: Medline, Embase, PsychINFO, Web of Science, and CINAHL were searched until April 2020. Random-effect meta-analyses were applied. The I 2 statistic and the Egger's test assessed heterogeneity and publication bias.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 117 publications
(95 reference statements)
1
12
0
Order By: Relevance
“…Experiential avoidance was associated with NSSI in the univariate analyses, which is consistent with research showing that individuals who tend to avoid undesirable emotions are more likely to engage in NSSI (Angelakis & Gooding, 2021 ). Experiential avoidance was more strongly related to NSSI in the past year than NSSI history, which may suggest that experiential avoidance is particularly relevant for understanding recent rather than past engagement in NSSI (see Anderson & Crowther, 2012 ).…”
Section: Discussionsupporting
confidence: 88%
“…Experiential avoidance was associated with NSSI in the univariate analyses, which is consistent with research showing that individuals who tend to avoid undesirable emotions are more likely to engage in NSSI (Angelakis & Gooding, 2021 ). Experiential avoidance was more strongly related to NSSI in the past year than NSSI history, which may suggest that experiential avoidance is particularly relevant for understanding recent rather than past engagement in NSSI (see Anderson & Crowther, 2012 ).…”
Section: Discussionsupporting
confidence: 88%
“…When adverse events occur in their life, they have deviation in processing stimuli (especially negative information) and regard it as a threat, and tend to respond by injuring themselves. Additionally, recent evidence has implicated experiential avoidance (EA) as a potentially important factor in the engagement of NSSI behaviors and suicidal ideation [ 13 , 14 ]. The EA model posits that self-injury is regarded as an avoidance and escape behavior in response to unwanted and distressing cognitions or emotions, or experiences of uncontrollable negative emotional arousal.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the six core concepts of the psychological inflexibility model, and it reinforces psychological inflexibility, which is thought to be the root cause of human suffering and dysfunction ( Hayes et al, 2006 ; Dionne et al, 2013 ). Empirical research has found that experiential avoidance is not only associated with substance abuse ( Kheirabadi et al, 2021 ), eating disorders ( Litwin et al, 2017 ), self-injury ( Angelakis and Gooding, 2021 ), and other externalizing problems, it has also been shown to be associated with anxiety, compulsion, post-traumatic stress, and depression symptoms ( Tull et al, 2004 ; Orcutt et al, 2020 ; Akbari et al, 2022 ), all of which are related to mental health problems ( Peng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%